Mechanical induction of interleukin‐11 regulates osteoblastic/cementoblastic differentiation of human periodontal ligament stem/progenitor cells. (20th June 2014) - Monnouchi, S.; Maeda, H.; Yuda, A.; Hamano, S.; Wada, N.; Tomokiyo, A.; Koori, K.; Sugii, H.; Serita, S.; Akamine, A.
Abstract : Background and Objective: The periodontal ligament (PDL) is continually exposed to mechanical loading caused by mastication or occlusion. Physiological loading is thus considered a key regulator of PDL tissue homeostasis; however, it remains unclear how this occurs. We recently reported that an appropriate magnitude of mechanical stretch can maintain PDL tissue homeostasis via the renin–angiotensin system. In the present study, we investigated the expression of interleukin‐11 (IL‐11) in human primary PDL cells (HPDLCs) exposed to stretch loading, the contribution of angiotensin II (Ang II) to this event and the effects of IL‐11 on osteoblastic/cementoblastic differentiation of human PDL progenitor cells (cell line 1‐17). Material and Methods: Human primary PDL cells, derived from human tissues, with or without antagonists against the Ang II receptors AT1 or AT2, were subjected to cyclical stretch loading with 8% elongation for 1 h. Expression of IL‐11 was measured by ELISA in these cultures and by immunohistochemistry in the sectioned maxillae of rats. The osteoblastic/cementoblastic potential of cell line 1‐17 was determined using cell proliferation, gene expression and Alizarin Red staining. Results: Positive staining for IL‐11 was observed in the PDL of rat maxillae and in cultures of HPDLCs. In HPDLCs exposed to stretch, expression of the IL11 gene and the IL‐11 protein were up‐regulated, concomitant with an increase in Ang II and via AT2. Recombinant human IL‐11 (rhIL‐11) stimulated an increase in expression of mRNA for the cementoblast‐specific marker, CP‐23, and for the osteoblastic markers, osteopontin and bone sialoprotein, and promoted proliferation in cell line 1‐17. In addition, rhIL‐11 also increased the degree of mineralized nodule formation in cell line 1‐17 cultures treated with CaCl2 . Conclusion: Mechanical loading appears to control proliferation and osteoblastic/cementoblastic differentiation of human PDL stem/progenitor cells through the regulation of Ang II and AT2 by IL‐11.